Daily learning flow of inclusive education for Early Childhood - AKRIM, M.; HARFIANI, R. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACTThis study was aimed to analyze the daily learning flow of early childhood inclusive education. The study used qualitative research, with a phenomenological approach in RA. An-Nahl, Jakarta. The data collection techniques used in this study were observation, interviews, focus group discussions, and documentation; then, they are analyzed descriptively with an interactive analysis model. The results obtained were the daily learning flow plan in the form of pre-opener, opener, energizer, activity, linking and summarizing, review, mission, closer applied by RA. The conclusion of this study was the modification of the daily learning flow, which is the flagship characteristic of RA.RESUMENEste estudio tuvo como objetivo analizar el flujo de aprendizaje diario de la educación inclusiva en la primera infancia. El estudio utilizó investigación cualitativa, con un enfoque fenomenológico en la RA. An-Nahl, Yakarta. Las técnicas de recolección de datos utilizadas en este estudio fueron observación, entrevistas, discusiones de grupos focales y documentación; luego, se analizan descriptivamente con un modelo de análisis interactivo. Los resultados obtenidos fueron el plan de flujo de aprendizaje diario en forma de preaperturador, abridor, energizador, actividad, vinculación y resumen, revisión, misión, aplicación más cercana por RA. La conclusión de este estudio fue la modificación del flujo de aprendizaje diario, que es la característica principal de la RA.